Analisis Dan Perancangan Sistem Informasi Penilaian Kinerja Karyawan Pada PT. BPR Universal Sentosa - Natanael, Bixon; Mulyono, Herry (Jurnal Manajemen Sistem Informasi, 2017)
PT BPR Universal Sentosa yet have information technology systems performance appraisal computerized to facilitate the assessment of performance and data processing employees. In the performance appraisal process is done using the performance appraisal form be paper. To know the development of an assessment of employee performance, Ministry of HRD must recapitulate the results of the assessment of each period using office excel. The authors aim to analyze and design information systems by implementing the performance appraisal system of performance evaluation of web-based information. The framework of this study consisted of a literature review, data collection, data analysis, system development, and report generation. System development method the authors do design use case, activity diagrams, class diagrams as well as the waterfall model and prototype. Employee performance evaluation information system can perform the performance appraisal process and manage data employees well in order to streamline and streamline the performance appraisal process and accelerate time and minimize error rates when entering data. The author also expects the system is the development of more and officials who can be responsible in operating the system to prevent fraud.